2022
DOI: 10.3390/buildings12101749
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Urban Spatial Accessibility of Museums within the Scope of Seoul

Abstract: While urban accessibility of museums plays a crucial role in the growth of a cultural city, in reality, an uneven distribution of museums exists in cities. In particular, museums are concentrated in certain regions or located in a place that is different from the cognitive experience of local residents. To solve this issue, this study quantified the urban space of Seoul, which has entered into the status of a cultural city since the 1990s, as its target city by using space syntax. Further, a suitability analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…Users' movement and interaction patterns can be predicted [45,46]; 3. The robustness of the theory enables it to transform complex spatial arrangements into understandable data, allowing researchers to apply its principles to optimize shared spaces [47][48][49]. This optimization can increase cross-generational communication by promoting inclusive design, ensuring equitable access to shared resources, and fostering a sense of unity among residents of all ages.…”
Section: Methodsmentioning
confidence: 99%
“…Users' movement and interaction patterns can be predicted [45,46]; 3. The robustness of the theory enables it to transform complex spatial arrangements into understandable data, allowing researchers to apply its principles to optimize shared spaces [47][48][49]. This optimization can increase cross-generational communication by promoting inclusive design, ensuring equitable access to shared resources, and fostering a sense of unity among residents of all ages.…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the form and method of analysis, convex spaces or axial lines are used to quantitatively analyze the use and perception of each convex space (axial line) based on the spatial depth generated while using the space [33]. In particular, studies have already been conducted to analyze urban space using axial lines to understand urban hierarchy and review spatial accessibility [34,35], and many scholars have demonstrated that social and economic phenomena occurring in urban spaces can be interpreted using indicators related to space syntax [36][37][38]. Integration is an important indicator that describes the accessibility of space in space syntax; it is divided into two scales: global and local integration.…”
Section: Space Syntaxmentioning
confidence: 99%
“…Penelitian dan Zhang et al (2022) menunjukkan perencanaan spasial aksesibilitas pariwisata terbukti mampu meminimalisir biaya transportasi. Penelitian Zhao & Moon (2022) mengenai museum di Seoul menunjukkan bahwa wisatawan lebih menikmati atraksi pariwisata jika perencanaan spasialnya terintegrasi dengan rute angkutan umum. Lopes et al (2022) menambahkan, perencanaan spasial aksesibilitas pariwisata, terutama di ruang-ruang alami, turut berperan dalam pertumbuhan ekonomi masyarakat lokalnya.…”
Section: A Pendahuluanunclassified